Drying Characteristics and Shrinkage Model Analysis of Pitaya Heat Pump Drying - Lucong HAN; Tingxiang JIN; Zhenya ZHANG; Guanghong WANG; Jianxiu LIU (Shipin gongye ke-ji, 2023)
In order to optimize the pitaya heat pump drying process and improve the quality of dried products, the effects of drying temperature, slice thickness and relative humidity on heat pump drying characteristics and the volume ratio of pitaya were studied. The optimal shrinkage dynamic model was determined to predict the volume variation law under different heat pump drying conditions. The results demonstrated that the drying rate increased with the increase of drying temperature, the decrease of slice thickness and relative humidity. The drying temperature had the greatest effect on it while the slice thickness had the least. The volume ratio decreased with the increase of drying temperature and the decrease of slice thickness and relative humidity. Comparing and analyzing the five thin-layer drying models, the Quadratic model was determined as the most accurate to describe the volume ratio law in the pitaya heat pump drying process. The average error of the calculated value was 5.01% compared with the test value. Under the heat pump drying conditions described in this paper, the contraction activation energy of the pitaya was calculated to be 27.185 kJ/mol by Arrhenius equation. Based on the volume shrinkage model, the process parameters of heat pump drying could be optimized and the dry products with more appropriate volume could be obtained. This study could provide technical support for the volume shrinkage law of pitaya in the heat pump drying process.